INOVASI SOSIAL DAN BUDAYA DALAM PEMBERDAYAAN MASYARAKAT: STRATEGI UNTUK PEMBANGUNAN INKLUSIF DI KABUPATEN PONOROGO JAWA TIMUR - Syahrudin; Huda, Fatakhul; Faizah, Siti Khusnul (Journal of Islamic Science Community, 2024)
This study aims to analyze the role of social and cultural innovation in community empowerment as a strategy to realize inclusive development in Ponorogo Regency, East Java. Social innovation includes creative solutions designed to address social challenges through a collaborative community-based approach, while cultural innovation focuses on preserving, revitalizing, and developing local values as social and economic capital. This study uses a qualitative method with a case study approach, involving in-depth interviews with stakeholders, participant observation, and analysis of local policy documents. The results of the study show that various cultural-based innovation programs, such as the revitalization of Reog art and the development of cooperatives based on traditional values, contribute significantly to improving community welfare and strengthening social cohesion. Social innovation implemented through informal education and community-based creative economy programs has succeeded in creating jobs, increasing individual capacity, and reducing social inequality. However, the main challenges in implementing this innovation include limited resources, cultural resistance to change, and minimal infrastructure support. With the right strategy, social and cultural innovation can be a catalyst for inclusive development that involves all levels of society, creates active participation, and encourages local independence. The main recommendations of this study include strengthening synergies between government, community, and private sector, as well as developing policies that support the sustainability of innovation based on local wisdom. This study is expected to be a reference for the development of similar empowerment models in other regions, especially those with strong cultural and social potential.